Medical students' perceptions of professional misconduct: relationship with typology and year of programme. Issue 2 (5th August 2017) - Zulkifli, Juliana; Noel, Brad; Bennett, Deirdre; O'Flynn, Siun; O'Tuathaigh, Colm
Abstract : Aim: To examine the contribution of programme year and demographic factors to medical students' perceptions of evidence-based classification categories of professional misconduct. Methods: Students at an Irish medical school were administered a cross-sectional survey comprising 31 vignettes of professional misconduct, which mapped onto a 12-category classification system. Students scored each item using a 5-point Likert scale, where 1 represents the least severe form of misconduct and 5 the most severe. Results: Of the 1012 eligible respondents, 561 students completed the survey, providing a response rate of 55%. Items pertaining to disclosure of conflict of interest were ranked as the least severe examples of professional misconduct, and this perception was highest among finalyear students. While ratings of severity declined for items related to 'inappropriate conduct not in relation to patient' and 'inappropriate use of social media' between years 1 and 3, ratings for both categories increased again among clinical cycle (fourth and final year) students. Conclusions: Increased clinical exposure during years 4 and 5 of the undergraduate programme was associated with better recognition of the importance of selected professional domains. Disclosure of conflict of interest is identified as an area of medical professionalism that requires greater emphasis for students who are at the point of transition from student to doctor.